From recipe to research: introducing undergraduate students to the nature of science using a hybrid practical course centred on drug discovery for neglected diseases. Issue 6 (June 2021) - Wijtmans, Maikel; Edink, Ewald; van Linden, Oscar PJ; Zheng, Yang; Blaazer, Antoni R; Siderius, Marco; van Muijlwijk-Koezen, Jacqueline E
Graphical abstract: Highlights: A hybrid undergraduate laboratory course combines laboratory skills and exposure to research. Students experience the nature of science first-hand by synthesising hit derivatives. A neglected disease drug discovery project is well suited as research topic. A daily interactive session fosters scientific discussion amongst students. A hybrid practical course in synthetic medicinal chemistry was designed for second-year undergraduate students. The first half focused on techniques and skills, while the second half addressed a drug discovery setting in a research project on neglected diseases. A daily interactive plenary session allowed for thorough discussions among the students. Over four years, 187 students participated, and 68 pure compounds (many of which novel) were isolated and biologically tested. Evaluations by students and teachers were positive. The success of the hybrid practical course demonstrates how undergraduate students can be meaningfully engaged in the nature of science through a drug discovery project. Teaser: A hybrid undergraduate practical course involving synthetic medicinal chemistry on neglected diseases bridges the gap between skills, techniques and scientific research, and exposes students to the nature of science.